Towards climate change awareness through distance learning: are young portuguese and brazilian university students vigilant? - Caetano, Fernando J. P. (2018)
Although distance learning and e-learning are currently acknowledged as important training tools for higher education institutions, they are seldom used as a way of disseminating environmental sustainability, climate change and its implications. The work presented here is the result of a teamwork between two universities, one from Brazil and the other from Portugal, which joined efforts to promote an interdisciplinary massive open on-line course associated with the environmental sustainability. We have inquired young university students from these two countries in order to understand which are their main conceptions and ideas about the climate changes as well as proposals they have for its mitigation. From these dialogs, we observed that, irrespectively of the geographical distance/location, those young students, share similar concerns, conceptions and proposals but it is also noticeable a clear lack of scientific knowledge when discussing these topics. This is an important starting point for the creation of a set of learning resources accessible to different audiences and with different and diverse backgrounds that can stimulate the interest on scientific knowledge. In this context it is our believe that eLearning and distance education supported by the information technologies can efficiently and effectively contribute for a well-supported knowledge on environmental sustainability, namely climate changes its causes and effects.